Research Title: Impact of Inflation on South Sudan Economy Case study: Juba Main Market - South Sudan - Ayoker (PhD), Lam Bukeje (IJRDO - Journal of Business Management, 2021)
This study is carried out to investigate about the impact of inflation on South Sudan economy .The aims of this study to know the impact of inflation on south Sudan economy and money supply. The researcher used qualitative and quantitative methods for collected data and the data was analyzed by (SPSS) statistical package for social science. The researcher has reached to a numbers of findings: the study revealed mismanagement economics resources, high taxes rates, the study revealed that the inflation increases cost of living because of price increase, political instability in the country and devaluation of country currency, lack of feeding roads. The research suggested a number of important recommendations which are the following: the government should change the policy of depending on imported goods and services and encourage export of local products, bank of South Sudan should adopt strong monetary policy, government should combat corruption and implement transparency and accountability, government should encourage domestic production and small industries by giving loans and grants.